Implementation of Dakwah in the Era of Disruption: Implementasi Dakwah Pada Era Disrupsi - Ningrum, Millati Eka Setia; Astutik, Anita Puji (Indonesian Journal of Education Methods Development, 2023)
In its development, advanced technology is influenced in terms of economic, political, cultural, artistic and educational aspects. Internet is a medium that develops at a very high speed in this global technology era. There has been a shift from face-to-face sermons to sermons delivered by digital technology in recent years. The purpose of the research is to find out the implementation of da'wah in the era of disruption and to find out what factors cause the success and failure of digital da'wah media in the era of disruption. The method used is descriptive with a qualitative approach. The results of the study show that the implementation of Da'wah in the Era of Disruption in general, aspects of Islamic da'wah teachings consisting of aqidah, shari'ah, muamalah and morals have been widely taught. Then the success and failure factors of digital da'wah media in the era of disruption. The success factor of digital da'wah media in the era of disruption is internet users. While the failure factor is the emergence of increasingly complex problems in society.